Evaluation of Chinese Scatterometer Ocean Surface Wind Data: Preliminary Analysis - Ke Zhao; Chaofang Zhao; Ge Chen (Earth and Space Science, 2021)
Abstract Three scatterometers have been launched in China including Haiyang‐2A scatterometer (HY‐2A/SCAT), Haiyang‐2B scatterometer (HY‐2B/SCAT), and China French Oceanography Satellite scatterometer (CFOSCAT). Both of HY‐2A/SCAT and HY‐2B/SCAT are rotating pencil‐beam scatterometers while CFOSCAT is the first rotating fan‐beam scatterometer (RFSCAT) in the world. In this study, we focus on the evaluation of Chinese scatterometer operational wind products from January 2019 to April 2019. Scatterometer wind products are collocated with buoy measurements. Error varieties under different atmospheric stratification conditions are also taken into consideration. The average biases and root mean square errors (RMSEs) between buoy and scatterometer data are basically satisfied with the scatterometer mission requirements (2 m/s and 20°). HY‐2B/SCAT wind products have the best data quality. However, HY‐2A/SCAT wind products have the largest deviations compared with buoy measurements and the wind direction RMSE was about 24.19°. The biases change a lot between different atmospheric stratification conditions. HY‐2A/SCAT winds have abnormal large deviations when wind speeds are higher than 10 m/s while HY‐2B/SCAT and CFOSCAT winds are stable under neutral conditions. In brief, the wind data quality of HY‐2B/SCAT is the best and then is CFOSCAT while HY‐2A/SCAT winds have the largest deviations and are unstable under different atmospheric stratification conditions. Atmospheric stratification impacts should be considered in wind retrieval and marine application.